Monitoring the impact of COVID-19 in Myanmar: Agricultural production and rural livelihoods in two irrigation schemes - August 2020 survey round - Lambrecht, Isabel B.; Ragasa, Catherine; Mahrt, Kristi; Aung, Zin Wai; Wang, Michael (International Food Policy Research Institute, 2020)
This policy note provides evidence of the immediate impacts of the COVID-19 crisis on farming communities in Myanmar’s Central Dry Zone using baseline data from January 2020 (BL) and followup telephone survey data. 1 The first round of the telephone survey was conducted with 606 households between 10 and 21 June 2020 (PS1) and inquired about the effects of COVID-19 on agricultural production and other livelihood sources from February to May 2020. The second round effects of COVID-19 in June and July.